SOLO MOTHERHOOD: A CULTURAL AND LEGAL APPROACH TO WOMEN'S RIGHTS IN BRAZIL (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
Throughout history, “single mothers” have faced social and legal stigmas, especially for not being part of a marital relationship, either because they raise their sons and daughters without the physical presence of the father, or because of the unequal division of motherhood. In view of this, through a deductive study based on a bibliographical study, the main objective involves reflecting on social and legal perspectives regarding motherhood and the rights of single mothers in Brazil. The study shows that although the 1988 Federal Constitution addresses equality between men and women in all areas, reality shows an incompatible scenario. In the case of motherhood, patriarchal culture continues to take charge of the sexual division of motherhood, which results in an overload for women and, consequently, affects their rights, as well as those of their children. In view of the above, legally, the issue appears to be more peaceful, while culturally, a constant fight against the ills of patriarchy is essential, aiming to understand that motherhood and fatherhood need to develop together.